Harmonious Labeling On Helm Graphs - Husnul Hatima; Nurdin Hinding; Muh Nur (Universitas Negeri Makassar, 2022)
graph consists of two sets, namely vertices and edges , which are sets that cannot be empty. The helmet graph is obtained from graph circle with addition side pendants with notation . Something graph side is said to be harmonious if there is an injective function that produces function labeling side which will result in a different sided label. In this thesis, graphs with odd and even results will be constructed as harmonious graphs. Where for every for odd helmet graph and for even helmet graph.